ALAT UKUR TDS (TOTAL DISSOLVED SOLID) AIR GARAM DENGAN RESISTIF SEBAGAI INDIKATOR - Dewa, Aloisius Wisnu Lalita; Sasmoko, Priyo (Vocational School Diponegoro University, 2016)
Aloisius Wisnu Lalita Dewa, Priyo Sasmoko Â in this paper explain that, physical water quality can be identified in various ways, one of which is measuring the amount of solute called Total Dissolved Solid (TDS). This study aims to design and make a TDS solution by using two electrodes as sensors. These two electrodes flow alternating current and negative values alternately into water. Analog signal in the form of voltage is read by the microcontroller by converting it into a digital signal, then the microcontroller processes the data and displays the TDS value. Tests are carried out by measuring the same solution using TDS meters and salt water TDS. Testing starts from a solution of 175 ppm to 8500 ppm. Making solutions based on TDS meter factory production. The results of salt water TDS measurements showed that the measured tds values increased from 173 ppm to 8007 ppm. Error reading at 8500 ppm, this is because the reading distance of salt water TDS is only up to 8260 ppm.Â Keywords : TDS, conductivity, electroda, measurement device.ReferencesMalvino. 1995. Prinsip-prinsip Elektronkai. Jakarta : Erlangga.Rusmadi, Dedy. 2001. Mengenal Komponen Elektronika. Bandung : Pionir JayaSumariyah, Yulianto. T, Priyono J, 2006. Rancang Bangun Sistem Pengukur Konduktivitas Larutan Elektrolit Menggunakan Mikrokontoler AT89C51. Program Studi Fisika Fakultas MIPA Universitas Diponegoro. Semarang.Utomo, D. 2012. Alat pengukur resistansi konduktivitas. dan Total dissolved solids air dengan Teknik dorong-tarik. Program Studi Sistem Komputer. Fakultas Teknik Elektronika dan Komputer. Universitas Kristen Satya Wacana. Salatiga.Wiono.A,Rahmawati. E, 2014.Â Perancangan Dan Pembuatan Alat Ukur Konduktivitas Larutan Berbasis Mikrokontroler. Program Studi Fisika Fakultas MIPA Universitas Negeri Surabaya. Surabaya